Chimpanzee Mindreading and the Value of Parsimonious Mental Models. (September 2015) - Clatterbuck, Hayley
Abstract I analyze two recent parsimony arguments that have been offered to break the current impasse in the chimpanzee mindreading controversy, the 'logical problem' argument from Povinelli, Penn, and Vonk, and Sober's attempt to apply model selection criteria in support of the mindreading hypothesis. I argue that Sober's approach fails to adequately rebut the 'logical problem'. However, applying model selection criteria to chimpanzees' own mental models of behavior does yield a response to the 'logical problem' and reveals an adaptive advantage of mindreading models and a potential solution to a paradox raised by Whiten.